Patterns and forms of place and its characteristics in the poetry of Husseini lamentation among contemporary poets: an analytical study - Alrubye, Taghreed; Mohammed, Karar (Al-Adab Journal, 2023)
The work on analyzing the dimensions of the poetic place, its aesthetics, characteristics and patterns, is one of the critical trends that coincided with the development of the mechanisms of critical work on the poetic text in the modern era. Al-Husseini among contemporary poets, through the selection of certain poetic "models" that express, with their contents, the characteristics and characteristics of this trend in the circle of this poetry.The importance of this research stems from the fact that it attempts to monitor the dimensions of renewal in the poetry of the contemporary Husseini lamentation, because recalling the place and employing it as a dominant structure in the circle of this poetry has greatly enriched the development of the dimensions of the contemporary Husseini poem, whether at the semantic, stylistic or at the level of The nature of poetic language and its ability to re-create the figurative and allegorical dimension of the place.The most important patterns of place that were treated - within the limits of this research - and monitored them as prominent phenomena in the poetry of Al-Husseini lamentation among contemporary poets, were represented by two basic levels: the level of the real place, which appeared in two basic dimensions, namely the historical place and the natural place, and the other level: is the imagined place and its most prominent applications It was in the circle of Al-Husayni’s lamentation poetry among contemporary poets, represented by the symbolic place pattern, and the subjective/psychological place pattern.. The research was not satisfied with extracting and defining such spatial patterns, but also tried to extract the characteristics and characteristics of each place and its difference from others, especially when the Husseini poet tries to employ His data according to the determinants of poetic vision within the poem.